Double bass and electric bass: the case study of John Patitucci - Cavalli, Massimo (2016)
The electric bass and double bass are two different instruments sharing a common function: they link harmony with rhythm, especially when talking about jazz music. The capacity of a bassist to fully support an ensemble is something that can be achieved individually playing electric or double bass. However there are some bassists who, despite of the technical differences between these two instruments, choose to play both. Some of these performers are true masters using and switching electric and double bass according to the different musical settings. It is possible to define similarities and differences between the electric and double bass, but is it viable to use similar approaches too? In order to investigate this field, I focus my research on one exemplar player who combines all the qualities needed to both play electric than double bass: John Patitucci, an inspiration for bassists of all generations and a musician who synthesizes all the fundamental characteristics of an ideal bass player. This dissertation is inspired by Patitucci’s example and by the urge to fill a gap in the specialized literature concerning the history and application of different left and right hand techniques on the electric and double bass. The main purpose of this study is to create the backbone of a bass program for teaching both instruments using John Patitucci as example. His technical approach on both instruments and his soloing vocabulary are points of departure of this dissertation. I begin my study with the historical origins of Patitucci’s techniques ending with the development of exercises created in order to teach his techniques and vocabulary to those who aspire to play electric and double bass; RESUMO: Baixo elétrico e contrabaixo, dois instrumentos distintos que partilham uma função comum: a possibilidade de produzir um conjunto de notas capazes de interligar uma grelha harmonia a uma base rítmica, criando uma coesão estética e musical, sobretudo na música jazz. A capacidade de um baixista de conseguir alcançar de forma eficiente esta ligação como sólido suporte para um “ensemble” musical está na base de uma sua eventual afirmação profissional. Há músicos que apesar das diferencias técnicas entre estes dois instrumentos, decidiram tocar ambos; alguns deles conseguiram destacarse, usando e trocando o baixo elétrico e o contrabaixo para servir melhor diferentes situações musicais. O contrabaixo e baixo elétrico têm características em comum mas ao mesmo tempo diferem por apresentar algumas diferenças técnica substanciais; será por isso possível abordar, explorar e aprender ambos utilizando uma mesma base metodológica? Com o intuito de explorar esta possibilidade direcionei a minha pesquisa para o estudo de um músico que no curso da sua longa carreira consegui grande destaque em quanto baixista elétrico e contrabaixista. John Patitucci é a síntese desta tipologia de músico, sendo uma fonte de inspiração para baixistas de todas as gerações. Esta dissertação é inspirada no seu exemplo e no desejo de colmatar o vazio presente na literatura musical comum aos dois instrumentos sobre a história e aplicação das técnicas da mão esquerda e direita. O foco principal é a criação de uma base sólida para o futuro desenvolvimento de um programa de ensino comum para o baixo eléctrico e o contrabaixo, utilizando o vocabulário técnico e improvisativo de Patitucci como ponto de partida. A dissertação aborda as origens históricas das técnicas utilizadas por Patitucci desenvolvendo, numa fase sucessiva, exercícios criados com a função de ensinar as suas técnicas aos que desejarem aprofundar a prática do baixo elétrico e do contrabaixo.